2020
DOI: 10.1016/j.msea.2020.139409
|View full text |Cite
|
Sign up to set email alerts
|

Structures and mechanical properties of Ti-Nb-Cr-V-Ni-Al refractory high entropy alloys

Abstract: Four refractory high entropy alloys with different chemical compositions, which can be calculated as Ti (50-1.5625x) Nb (30-0.9375x) Cr 10 V 10 Ni 1.5x Al x (x ¼ 0, 5, 7, 10), were prepared by arc melting to determine the effect of Ni and Al on the phase composition, structure and mechanical properties. Each alloy was studied in both the as-cast and annealed at 1000 � C for 24 h conditions; compression tests at room temperature or at 800 � C was used to examine mechanical behavior of the alloys and the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 62 publications
(80 reference statements)
1
16
0
1
Order By: Relevance
“…According to the constitutive elements and the composition of the sigma phases for present alloys, the atomic structure of possible sigma phase is believed to be Al(Nb, Co) 2 and Al(Nb, Ni) 2 phases, since sigma phases in current alloys are enriched with Nb, Al, Ni, and Co. Note that the AlNb 2 sigma phase also could contain ~11.4 at.% of Co, ~30 at.% of Ti, ~20 at.% of V, or ~10 at.% of Ni as solute elements [ 18 , 31 , 32 ]. Furthermore, the formation of AlNb 2 sigma phase was often observed in Al-Nb-Ti-V HEAs at temperatures below 1200 °C, but the fraction was very limited [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the constitutive elements and the composition of the sigma phases for present alloys, the atomic structure of possible sigma phase is believed to be Al(Nb, Co) 2 and Al(Nb, Ni) 2 phases, since sigma phases in current alloys are enriched with Nb, Al, Ni, and Co. Note that the AlNb 2 sigma phase also could contain ~11.4 at.% of Co, ~30 at.% of Ti, ~20 at.% of V, or ~10 at.% of Ni as solute elements [ 18 , 31 , 32 ]. Furthermore, the formation of AlNb 2 sigma phase was often observed in Al-Nb-Ti-V HEAs at temperatures below 1200 °C, but the fraction was very limited [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the addition of Co or Ni stimulates the homogeneously distributed sigma precipitates in the BCC solid-solution matrix, and it was demonstrated that the sigma precipitate plays a crucial role in the improved yield strength at room and elevated temperatures. There have been extensive efforts to improve the yield strength of RHEAs by controlling the size, volume fraction, and the feature of precipitates' distribution [18,36,37], and it has been reported that the homogeneous distribution of fine precipitates is effective to improve the strength [37] compared to other control factors. As observed in the current case, the uniformly dispersed sigma precipitates in the Al 0.8 NbTiVM 0.2 (M = Co, Ni) alloys are believed to improve the yield strength at room and high temperatures.…”
Section: Microstructure and Mechanical Properties Of The Al08nbtivm02 (M = Co Ni) Alloys Heat-treated At 1100 °C For 1 Hmentioning
confidence: 99%
See 2 more Smart Citations
“…These BCC, sigma, and Ti2Ni phases were found to improve the material's mechanical characteristics, and the nanoindention of those phases is shown in Table 3 [39]. Panina et al reported that yield strength and ultimate tensile strength improved after replacement [39]. NbTaTiV refractory high-entropy alloys were synthesized using powder metallurgy as the sintering temperature was increased from 1500 to 1700 °C, and the Vickers hardness increased (as shown in Figure 2) [31].…”
Section: Mechanical Behaviormentioning
confidence: 99%